(untitled) (Research, Society and Development, 2022)
The main instrument of municipal urban planning in Brazil are the Master Plans (PD). They provide the guiding guidelines for the city’s urban growth. By law, every municipality with more than 20 thousand inhabitants, with public interest, tourist and environmental potential or with environmentally degraded areas must have a PD, prepared in a participatory way, involving all segments of the population. This article presents partial results of studies carried out in a city in the interior of Ceará, called Carnaubal, with an estimated population of about 17,763 inhabitants, located in the administrative region of Ibiapaba. The proposal for technical assistance in the elaboration of the PD of Carnaubal arose at the request of a former student and councilor who showed interest and concern with the planning of her city, even though there was no legal requirement for its elaboration, understanding this discussion as fundamental and urgent. for the balanced development of the municipality. Based on this initiative, the research group Urbanism Collaborative - UrbColab, linked to the Center for Research in Architecture, City and Technology - NuPACT, started this experience involving students of architecture and urbanism, professors, professionals and the population, using various methods, such as sensitization of the technical staff of the region, technical surveys and community readings. This article aims to briefly present some of the results achieved and bring to light the reflection of how the academy can be allied to the public sector, collaborating for a construction of technical material.